BIOCHEMICAL PROFILE OF EMBRYONIC AND NON-EMBRYONIC CALLUS OF CLERODENDRUM PHLOMIDIS L. (International Association of Biologicals and Computational Digest, 2022)
Clerodendrum phlomidis L. (Arani) is a medicinal plant used in the treatment of Diabetes mellitus. Enzymatic studies helps to differentiate between embryonic and non-embryonic callus at very early stage. In vitro experiments were conducted using leaf, stem, node, internode, apical bud as an explant. Callus cultured on MS basal medium supplemented with various combinations of 2, 4-D and Kinetin (1 : 1, 2 : 2, 3 : 3, 4 : 4, 5 : 5 mg/l 2,4-D : Kinetin). Large variations were observed in the callus cultures owing to hormonal variations. Higher hormonal concentration 5 mg/l 2, 4-D + 5 mg/l kinetin resulted in somatic embryoids while lower concentrations 1:1, 2:2, 3:3 mg/l, 2,4-D : kinetin resulted in non-embryonic cells. Enzymatic activities of peroxidase, IAA- oxidase, invertase, protease,  and  amylase, polyphenol oxidase (PPO), catalase and enzyme protein were estimated from cytoplasmic as well as wall-bound fractions of 2, 4, 6and 8 week old callus using standard methods. In two week old culture peroxidase and polyphenol oxidase (both wall bound and cytoplasmic) activity increases in non-embryonic callus and decreases in embryonic callus while IAA oxidase and Protease (both wall bound and cytoplasmic) activity decreases in non-embryonic callus and increases in embryonic callus. Total amylase and α-amylase activity of wall bound enzymes increases in non-embryonic callus and decreases in embryonic callus while cytoplasmic activity decreases in non-embryonic callus and increases in embryonic callus. On the basis of the above study enzymes could serve as a biochemical marker to determine the embryonic and non-embryonic callus at very early stage.